The Dislocation of News Journalism: A Conceptual Framework for the Study of Epistemologies of Digital Journalism - Ekström, Mats (2019)
This article focuses on news journalism, social media platforms and power, and key implications for epistemology. The conceptual framework presented is intended to inspire and guide future studies relating to the emerging sub-field of journalism research that we refer to as “Epistemologies of Digital Journalism”. The article discusses the dependencies between news media and social media platforms (non-proprietary to the news media). The authority and democratic role of news journalism pivot on claims that it regularly provides accurate and verified public knowledge. However, how are the epistemic claims of news journalism and the practices of justifications affected by news journalism’s increased dependency on social media platforms? This is the overall question discussed in this article. It focuses on the intricate power dependencies between news media and social media platforms and proceeds to discuss implications for epistemology. It presents a three-fold approach differentiating between (1) articulated knowledge and truth claims, (2) justification in the journalism practices and (3) the acceptance/rejections of knowledge claims in audience activities. This approach facilitates a systematic analysis of how diverse aspects of epistemology interrelate with, and are sometimes conditioned by, the transformations of news and social media.